Right heart condition in patients with COVID-19 pneumonia - N. G. Poteshkina; N. S. Krylova; A. A. Karasev; T. A. Nikitina; A. M. Svanadze; I. P. Beloglazova; E. A. Kovalevskaya; K. A. Barakhanov; M. A. Lysenko; A. M. Ibragimova; V. N. Smorshchok (Российский кардиологический журнал)
Aim. To assess right heart condition in patients with coronavirus disease 2019 (COVID-19) pneumonia.Material and methods. One hundred and five patients with COVID-19 pneumonia were divided into 3 groups depending on the involvement of lung parenchyma: group I — 0-25%, II — 25-50%, III — 50-75%. The clinical status of patients was assessed using the NEWS2 and SHOKS-COVID scales. A complete blood count and biochemical blood tests were performed to determine the level of N-terminal pro-brain natriuretic peptide (NT-proBNP) and troponin I. Echocardiography was performed to assess the right heart structural, hemodynamic and functional parameters.Results. In patients with COVID-19 pneumonia, with an increase in lung parenchyma involvement, the intensity of systemic inflammatory response increased: C-reactive protein, group I — (4 [1,9; 35] mg/l), in III — (70,5 [33; 144] mg/l) (pI-III=0,012); myocardial stress marker level increased: NT-proBNP, group I — 77 [48; 150] ng/l, group III — 165 [100; 287] ng/l (pI-III=0,047). The dependence of NT-proBNP on C-reactive protein level was revealed (r=0,335, p=0,03). Intergroup comparison did not reveal significant differences between the main right heart functional parameters: TAPSE, Tei index (PW and TDI), FAC of the right ventricle (RV) (p>0,05). However, differences in the tricuspid annular peaks were found as follows: group I — 0,14 [0,12; 0,14] m/s, group II — 0,14 [0,12; 0,15] m/s, group III — 0,16 [0,14; 0,17] m/s (pI-II=0,012, pI-III=0,014) and RV global longitudinal strain: group I — 19,63±7,72%, group III — 27,4±5,93% (pI-III=0,014). The relationship between the RV global longitudinal strain and SHOKS-COVID score was confirmed (r=0,381; p=0,024).Conclusion. Patients with COVID-19 pneumonia showed no signs of right heart dysfunction. The development of RV hyperfunction was noted. Most likely, this is a compensatory mechanism in response to acute RV afterload. NT-proBNP increase under conditions of an inflammatory response may indicate myocardial stress. The results obtained allow to expand our understanding of the right heart condition in patients with COVID-19 pneumonia.